TORTOR ILAH MAJETTER PADA MASYARAKAT SIMALUNGUN KAJIAN TERHADAP NILAI - Siti Khodijah (Gesture: Jurnal Seni Tari, 2017)
Tortor Ilah Majetter an entertainment dance originating from the area Simalungun are often present at the party Rondang Bittang. Tortor Ilah Majetter a Tortor Ilah/singing. This study aims to determine how Tortor Ilah Majetter in Simalungun of values. To discuss the purpose of the study above, use the theories related to the topic of this research is the theory of value is made up ofreligious values, aesthetic values, social values, ethics values. Time spent in discussing Tortor Ilah Majetter in Simalungun of values research on the study of public during three monhs from june 2016 to august 2016. The location where the research is desa Purba Tongah Kecamatan Purba, Kabupaten Simalungun, Sumatera Utara. Data analysis in this research use descriptive qualitative data collection techniques by observation, library research, interviews, and documentation. The result of research based on the data collected can be seen that Tortor Ilah Majetter a young dance game on the night when the bright moon full moon that came with the singing. Tortor Ilah Majetter describe the joy of young people Simalungun. Though not much in the range of motion, but Tortor Ilah Majetter have values which are : 1) religious values which can be seen through poetry, 2) social values can be seen through the movement made jointly and simultaneously indicating Simalungun society very closely in togetherness, 3) aesthetic values can be seen through the motions, the pattern of the floor is well ordered and tidy. But it also can be seen through clothing and makeup dancer, 4) ethical values can be seen through the motions, the pattern of the floor, the clothes are limits and rules.